Lower Level of Interleukin-6 and Hepcidin Found in Lower Density of Physical Exercise among Athlete During Pandemic of Covid-19 - Purwani, Deni; Sulistiawati, Sulistiawati; Purwanto, Bambang (Folia Medica Indonesiana, 2021)
The pandemic of Covid-19 affected entire daily human life worldwide, including sports activities among athletes. An athlete was pushed to suit their routine activities with a new health protocol for Covid-19 prevention. Some of them were programmed to train at home with a moderate density of exercise, but others were still in a high density of exercise. This study compared the serum level of hemoglobin (Hb), interleukin-6 (IL-6), and hepcidin among athletes with a high versus moderate exercise density training program during the pandemic. Thirty-four indoor soccer athletes of a soccer football school in Malang voluntarily registered as a subject. Half of them received moderate exercise density exercise programs, and others received high-density exercise programs during June-July 2020. Interleukin-6 and hepcidin level mean was found significantly lower in the moderate group compared to the high-density group. Hemoglobin level mean was found not different between those groups. The lower density of exercise influenced on IL-6 and hepcidin serum level of athlete, but not on hemoglobin level.